Identity of nonlinear models to compare growth curves of the cattle breed Tabapuã - Carneiro, Antonio Policarpo Souza; Muniz, Joel Augusto; Carneiro, Paulo Luiz Souza; Malhado, Carlos Henrique Mendes; Martins Filho, Raimundo; Silva, Fabyano Fonseca e (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the use of identity of nonlinear models to compare growth curves of the cattle breed Tabapuã, between five production regions from Northeast Brazil. Weight data of 3,695 males and 4,236 females from Maranhão, Gado Algodão, Mata Agreste, Sertão, and Itapetinga‑Valadares regions were analyzed. After adjusting the Brody model, the likelihood ratio test was applied, with a chi‑square approximation, to evaluate the equality of parameters of growth curves between those regions. The reduced model with equal rate of maturity for some regions, with 14 parameters, was the most appropriate for describing animal growth. Curves of male growth showed maturity rates in common in the following regions of production: Gado Algodão and Mata Agreste, Maranhão and Itapetinga‑Valadares, and Sertão. For females, regions with maturity rates in common were: Mata Agreste and Sertão, Maranhão and Itapetinga‑Valadares, and Gado Algodão. The use of a single curve is not appropriate to describe the growth of the cattle breed Tabapuã in the studied regions.